A new class of copulas with tail dependence and a generalized tail dependence estimator - Matthias J. Fischer; Gerd Hinzmann (Friedrich-Alexander-Universität Erlangen-Nürnburg, Lehrstuhl für Statistik und Ökonometrie, 2006)
We present a new family of copulas (generalized mean copulas) which is positive comprehensive and allows for upper tail dependence. It includes the Spearman copula and a specific Fréchet copula as special cases. Some properties and a generalized tail dependence estimator are derived. Finally, a small simulation study is conducted.
Keywords: 330; Geometric mean; arithmetic mean; copula; tail dependence